2018
DOI: 10.1002/dac.3576
|View full text |Cite
|
Sign up to set email alerts
|

A performance comparison of measurement matrices in compressive sensing

Abstract: Summary Compressive sensing involves 3 main processes: signal sparse representation, linear encoding or measurement collection, and nonlinear decoding or sparse recovery. In the measurement process, a measurement matrix is used to sample only the components that best represent the signal. The choice of the measurement matrix has an important impact on the accuracy and the processing time of the sparse recovery process. Hence, the design of accurate measurement matrices is of vital importance in compressive sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 63 publications
0
75
0
Order By: Relevance
“…Candes and Tao proved that the Gaussian random matrix [2, 21, 22] with independent identically distribution can be a universal measurement matrix. Therefore, the measurement matrices in these experiments are the Gaussian random matrix with the size of m × n .…”
Section: Methodsmentioning
confidence: 99%
“…Candes and Tao proved that the Gaussian random matrix [2, 21, 22] with independent identically distribution can be a universal measurement matrix. Therefore, the measurement matrices in these experiments are the Gaussian random matrix with the size of m × n .…”
Section: Methodsmentioning
confidence: 99%
“…In [9], the authors compared the efficiency of their recovery algorithm using the mean square error. In [10], the authors compared the performance of the sampling matrices using metrics, namely recovery error, processing time, recovery time, covariance, and phase transition diagram. In [11], the authors evaluated the compressive sensing technique based on the recovery success rate, reconstruction error, recovery time, compression ratio, and processing time.…”
Section: Introductionmentioning
confidence: 99%
“…() Deterministic matrices have an advantage over random ones since they are easier to generate and store, which reduces the complexity of the system . It has also been shown that deterministic matrices speed up the reconstruction process . In any case, the sensing matrix must be known in order for the signal to be reconstructed.…”
Section: Introductionmentioning
confidence: 99%
“…11 It has also been shown that deterministic matrices speed up the reconstruction process. 10 In any case, the sensing matrix must be known in order for the signal to be reconstructed. This means that, in a collaborative network, the sensing matrix must either be fixed or be actively shared among the nodes of the network, which is the motivation for using chaotic matrices in this paper.…”
Section: Introduction Figurementioning
confidence: 99%